Genetic diversity analysis of Indian buffalo breeds By microsatellite markers - Rupinder; M. L. Sangwan (Journal of Livestock Biodiversity, 2025)
The present study was conducted on 20 unrelated animals each of Bhadawari and Murrah breeds to estimate genetic diversity parameters by microsatellite markers. Ten microsatellites markers recommended by FAO for buffalo diversity were used. The number of alleles in both the breeds per locus ranged from 3 to 6. The average numbers of alleles were 4.2 ± 0.38 for Bhadawari and 4.2 ± 0.44 for Murrah breed. The mean observed heterozygosity was 0.49 for Bhadawari and 0.53 for Murrah breed. The average expected heterozygosity was 0.57 and 0.59 for Bhadawari and Murrah breed, respectively. The observed heterozygosity values in both breeds were lowest for the loci ILSTLS008 and CSSM029. The overall mean heterozygosity in both breeds was 0.51. The average PIC value for all loci was 0.51 in Bhadawari and 0.52 in Murrah breeds. In the present study, 70 per cent of the microsatellite markers were found to be highly informative. Seven loci showed deviations from the HWE for the loci ILSTLS008, BRN, CSSM029, CSSM019, CSSM036, CSSM047 and CSSM038. The mean FIS, FIT and FST for all loci was – 0.12, 0.16 and 0.04, respectively. The standard genetic distance (Ds) between Bhadawari and Murrah breeds was 0.13 and the genetic identify was 0.88.